Probing Deviation of Adhered Membrane Dynamics between Reconstituted Liposome and Cellular System. Issue 24 (8th July 2019) - Mondal, Prasenjit; Chowdhury, Rajdeep; Nandi, Somen; Amin, Md. Asif; Bhattacharyya, Kankan; Ghosh, Surajit
Abstract: The dynamics of cell‐cell adhesion are complicated due to complexities in cellular interactions and intra‐membrane interactions. In the present work, we have reconstituted a liposome‐based model system to mimic the cell‐cell adhesion process. Our model liposome system consists of one fluorescein‐tagged and one TRITC (tetramethyl‐rhodamine isothiocyanate)‐tagged liposome, adhered through biotin‐neutravidin interaction. We monitored the adhesion process in liposomes using Förster Resonance Energy Transfer (FRET) between fluorescein (donor) and TRITC (acceptor). Occurrence of FRET is confirmed by the decrease in donor lifetime as well as distinct rise time of the acceptor fluorescence. Interestingly, the acceptor's emission exhibits fluctuations in the range of ≈3±1 s. This may be attributed to structural oscillations associated in two adhered liposomes arising from the flexible nature of biotin‐neutravidin interaction. We have compared the dynamics in a cell‐mimicking liposome system with that in an in vitro live cell system. In the adhered live cell system, we used CPM (7‐diethylamino‐3‐(4‐maleimido‐phenyl)‐4‐methylcoumarin, donor) and nile red (acceptor), which are known to stain the membrane of CHO (Chinese Hamster Ovary) cells. The dynamics of the adhered membranes of two live CHO cells were observed through FRET between CPM and nile red. The acceptor fluorescence intensity exhibits an oscillation in the time‐scale of ≈1±0.75 s, which is faster compared to the reconstituted liposome system, indicating the contributions and involvement of multiple dynamic protein complexes around the cell membrane. This study offers simple reconstituted model systems to understand the complex membrane dynamics using a FRET‐based physical chemistry approach. Abstract : The membrane dynamics of two adhered liposome‐based model and live cell systems are studied by using FRET, revealing an intermittent structural oscillation at the adhered region. The difference of adhered membrane dynamics between reconstituted liposome system and the in vitro cellular system has long‐term implications for gaining deeper physicochemical insights and a better understanding of the dynamics of complex membrane proteins.